THE ROLE OF KYAI’S LEADERSHIP IN STRENGTHENING SANTRI’S DISCIPLINARY CHARACTER BASED ON REWARD AND PUNISHMENT - Ashni Fannida Istina’ima Putri; Sukarman Sukarman; Muhammad Khoiruddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The disciplinary character of santri constitutes a critical foundation within pesantren-based Islamic education, essential for molding individual character, responsibility, and moral integrity. This study aims to investigate the strategic role of a Kyai's leadership in conceptualizing, planning, and implementing a balanced system of rewards and punishments to cultivate sustainable internal discipline among santri. Conducted at Pondok Pesantren Daarusy Syifa Al-Islami in Kudus, Central Java, this research utilizes a qualitative descriptive approach, departing from traditional pure library methods to capture empirical data through field triangulation. Data collection techniques comprise semi-structured interviews with the Kyai, administrators, teachers, and santri, alongside direct field observation and comprehensive documentary analysis. The findings reveal that the Kyai exercises a vision-driven, transformational style of leadership, serving as a primary moral model and strategic architect. The implementation of rewards includes social praise, public acknowledgment, and motivational privileges, which reinforce positive behavior. Conversely, punishments are executed through educational, non-physical sanctions designed to induce behavioral reflection and regular self-correction rather than mere superficial compliance. The integration of these dual approaches successfully bridges external compliance with internal moral consciousness, ensuring that discipline becomes a core personal value aligned with the national character-building framework.